Proyecto de factibilidad para la creacion de una empresa productora de barras de chocolate dulce y su comercializacion en la provincia de Zamora Chinchipe - Quezada Banegas, Kleber Isaías (2017)
The general objective of the present investigation tried of: TO DETERMINE THE FEASIBILITY OF THE CREATION OF A COMPANY PRODUCER AND COMERCIALIZADORA OF BARS OF SWEET CHOCOLATE IN THE COUNTY DE ZAMORA CHINCHIPE., with this purpose the different studies were elaborated that have allowed to determine this feasibility. To get the work investigative different methods they were used as the Scientist, deductive, inductive, analytic, synthetic, descriptive and the statistical one that you/they facilitated the realization of the investigation, among the techniques of summary of information was used the direct observation the interview and the survey applied Zamora's population that consisted. For that that after the application of 394 surveys, according to the size of the sample, it was determined that a consumption exists per capita or consumption for family of 210 units of 25 grams and an effective annual demand of: 4.801.743,58 units: with an offer of 64800 units and the unsatisfied demand throws a result of 4.736.943,58 units for the year it bases. When carrying out the technical study you verifies a capacity to use of the machinery of 8.22% of their installed capacity what projects a production of 1 704.000 annual units, with the same one that was possible to satisfy 35.97% of the unsatisfied demand. By means of a rating womb for points decided on the best location to lift the project, being in the neighborhood main street WHISTLES Iván Riofrio, taking into account that it is a semi-rural place and it has all the facilities for the production and execution of the activities. In the organizational study it is appreciated that the company had all the structural levels hierarchical flowcharts, posicional, functional and manual of functions. Having a payroll of 13 people's employees also conformed to for three partners and it will be legally constituted under the name of company of limited society "CHOCOYAN CIA LTDA" In the economic study you defines that it is necessary an initial investment of 99.720,91 dollars, divided in active fixed, $ 73.492,98 differed, $ 905,12 and circulating, $ 25.322,82 respectively. This investment was financed with an own capital corresponding to 72.01% and with a productive credit in the National Bank of Development corresponding to 25,07%: this credit will have an interest of 11 annual% and term will contract for three years with quotas trimestrales. The production cost for the first year is of 310.760,96 that it determines an unitary cost of production of 0.18USD for each product unit with a weight of 25 grams, taking into account an annual production of 1.704000 units. Being an I mount of revenues of 419.527,29 dollars, that that in the state of results or of losses and earnings it throws an utility it liquidates of 62.404,68 dollars in the first year. In the analysis of the balance point for the first year, the company should work to 46.51% of its used capacity and to maintain its sales in 195.129.00 dollars. The study or financial evaluation allowed to know the box flows in which the first year is of 73.631,31 dollars and consecutively the following years they show positive results. According to the box flows and a factor of upgrade of 5.83% VAN of the project is of 710.553.78 dollars, the relationship of benefit - cost determines a recovery of 0,32 cents for each invested dollar; the Period of capital recovery is of 1 year more 8 months and 1 days, likewise the Rate Internal Return is of 76,80%; as for the analysis of sensibility the project supports an increment of its costs in 28%, and a decrease of its entrance of 20.20%; with these values the analysis of sensibility is smaller at 1. The results of the financial reasons are positive what demonstrates the feasibility of the project. Later on he/she thinks about the conclusions and more significant recommendations of the investigation.